The effect of special additives on the physico-mechanical properties of mixtures used for the manufacture of cores by the cold-box-amine-process - S. V. Koreniugin; S. L. Rovin (Литьë и металлургия, 2023)
The article presents an analysis of the effect of various special additives on the physical and mechanical properties of sand‑resin mixtures used for the manufacture of cores by the cold‑box‑amine process. Two groups of additives that have the most significant effect on the thermal conductivity of mixtures were studied: additives containing metals or their oxides and carboncontaining additives and composites. The influence of these additives on the tensile strength of the mixtures in the cured state, on their gas content and gas permeability was determined, the results obtained were compared with the characteristics of the reference mixture made without the use of additives.